2015
DOI: 10.1016/j.ab.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of preanalytical variables on the stability of the human plasma proteome

Abstract: High quality clinical biospecimens are vital for biomarker discovery, verification, and validation. Variations in blood processing and handling can affect protein abundances and assay reliability. Using an untargeted LC-MS approach, we systematically measured the impact of preanalytical variables on the plasma proteome. Time prior to processing was the only variable that affected the plasma protein levels. LC-MS quantification showed that preprocessing times <6 h had minimal effects on the immunodepleted plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…Similar results were obtained with plasma samples from the same subjects (Figure S5). These results are consistent with conclusions of proteomics studies observing no significant changes in serum and plasma long‐term storage at −80°C .…”
Section: Resultssupporting
confidence: 92%
“…Similar results were obtained with plasma samples from the same subjects (Figure S5). These results are consistent with conclusions of proteomics studies observing no significant changes in serum and plasma long‐term storage at −80°C .…”
Section: Resultssupporting
confidence: 92%
“…Especially in case-control studies, any difference in the collection and processing of samples may result in systematic bias. So far, relatively little attention has been paid to this crucial aspect on a proteome-wide scale and these studies mainly investigate preanalytical effects (Rai et al, 2005;Timms et al, 2007;Schrohl et al, 2008;Qundos et al, 2013;Hassis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sample handling is a vital consideration in the search for differentially abundant proteins. Hassis et al used iTRAQ to evaluate the effects of pre‐analytical variables on the stability of the plasma proteome . They determined the influence of the time delay (0.5, 6, and 96 h) and temperature (RT & 37°C) before processing, freeze thaw cycles and long term storage (14–17 years).…”
Section: Methodsmentioning
confidence: 99%
“…Hassis et al used iTRAQ to evaluate the effects of pre-analytical variables on the stability of the plasma proteome. 28 They determined the influence of the time delay (0.5, 6, and 96 h) and temperature (RT & 37°C) before processing, freeze thaw cycles and long term storage (14-17 years). They concluded that the time prior to processing was the most significant variable.…”
Section: Labeling and General Protocolsmentioning
confidence: 99%